Globalization of Education, Opportunities and Prospects of Exporting Russian Education in Conditions of Sanctions Against the Russion Federation - M. E. Kosov (Вестник Российского экономического университета имени Г. В. Плеханова)
The present research studies specific features of globalization in education and export of services illustrated by universities and higher education institutions in countries holding the leading positions on the global education market, such as Great Britain, France, German, China and others. The research methodology is based on general and specific methods of cognition, on the analysis of methodological approaches and theoretical models of education service export, on the empiric approach to identifying peculiarities of country policy in the aspect of education globalization and related risks. The article provides conclusions concerning feasibility of using some of them in Russian universities and other higher education institutions. The author put forward a set of steps and recommendations aimed at raising the potential of education service export in Russia. It is possible that the use of conclusions and recommendations made by the research, in addition to work being done by universities could improve efficiency of their international activity as a ‘soft power’, which responds to interests of the university, the entity of the Russian Federation and geopolitical goals of Russia with regard to the current sanction pressure.